2012
DOI: 10.2147/opth.s24425
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of visual performance in 70 eyes implanted with the Tecnis® ZMB00 multifocal intraocular lens

Abstract: PurposeTo evaluate the development of visual acuity, dysphotopsia phenomena, and subjective sensations in patients implanted with the Tecnis® ZMB00 (Advanced Medical Optics Inc, Santa Ana, CA) multifocal intraocular lens.MethodsIn a sample of 70 eyes, distance and near visual acuity, with and without correction, contrast sensitivity, and patient satisfaction, were analyzed at 15, 30, and 60 days post-surgery.ResultsMean uncorrected distance visual acuity (logarithm of minimum angle of resolution) at 15, 30, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 21 publications
9
12
0
Order By: Relevance
“…Mean binocular logMAR UDVA in the current series was −0.10 at 6 months after surgery, which confirms the ability of this multifocal IOL to successfully restore distance vision, consistent with reports by other authors using the same type of multifocal IOL [3,4]. Specifically, Bautista et al [3] found a mean postoperative logMAR UDVA of 0.08 at 2 months postoperatively, and Friedrich [4] reported that 94.7% of patients implanted with the same IOL used in our study had a binocular UDVA of 0.1 LogMAR or better.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Mean binocular logMAR UDVA in the current series was −0.10 at 6 months after surgery, which confirms the ability of this multifocal IOL to successfully restore distance vision, consistent with reports by other authors using the same type of multifocal IOL [3,4]. Specifically, Bautista et al [3] found a mean postoperative logMAR UDVA of 0.08 at 2 months postoperatively, and Friedrich [4] reported that 94.7% of patients implanted with the same IOL used in our study had a binocular UDVA of 0.1 LogMAR or better.…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, Bautista et al [3] found a mean postoperative logMAR UDVA of 0.08 at 2 months postoperatively, and Friedrich [4] reported that 94.7% of patients implanted with the same IOL used in our study had a binocular UDVA of 0.1 LogMAR or better. The good distance vision outcome obtained in the current and previous studies is accompanied by a predictable correction of ocular refraction, resulting in minimum residual refractive errors.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Indeed, almost all eyes (30 eyes, 96.8%) had a postoperative spherical equivalent within ±1.00 D. Similar visual and refractive results were obtained by Bautista et al [11] using the same modality of diffractive IOL and by other authors [2, 3, 4] using other types of diffractive multifocal IOLs. Specifically, Bautista et al [11] found in a sample of 70 eyes of 70 patients a mean far LogMAR UCVA of 0.194 ± 0.054, 0.119 ± 0.026, and 0.076 ± 0.014 at 15, 30, and 60 days after surgery, respectively. In addition, these authors found that 74.3% of eyes had a far UCVA of 0.1 LogMAR or better at 60 days after surgery [11].…”
Section: Resultssupporting
confidence: 83%
“…With increased SA after myopic LASIK [14, 16, 27], we expected that an aspheric IOL with a more negative SA value can provide better mesopic vision. The Tecnis MIOLs correct for +0.27  μ m of SA [19, 28, 29] while the 809M corrects only for +0.18  μ m (Carl Zeiss Meditec AG, email communication, 2015) and the SN60D3 does not correct for any. This might explain the better mesopic CDVA in the current study.…”
Section: Discussionmentioning
confidence: 99%